2016
DOI: 10.3171/2016.2.spine151472
|View full text |Cite
|
Sign up to set email alerts
|

Can the anxiety domain of EQ-5D and mental health items from SF-36 help predict outcomes after surgery for lumbar degenerative disorders?

Abstract: OBJECTIVE Studies have shown that anxious or depressed patients may have poorer outcomes after lumbar fusion. These conclusions were drawn from questionnaires specifically designed to measure anxiety and depression. The objective of this study is to determine if responses to the EQ-5D anxiety/depression domain or the items used to calculate the 36-Item Short-Form Health Survey (SF-36) Mental Component Summary (MCS) can predict outcomes after lumbar fusion surgery. Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 19 publications
0
17
0
Order By: Relevance
“…It has been shown that objective functional tests are more robust against the influence of mental health status than a PROM. 1,25 Moreover, patients prefer performing an objective functional test over completing a battery of PROMs, perhaps because it provides direct and tangible feedback and is less time-consuming. 15 Considering these factors, the 5R-STS may constitute an excellent follow-up tool that could even be performed by patients themselves at home, either unsupervised or with televised supervision.…”
Section: Fig 4 Scatterplots With Marginal Histograms Showing Logarimentioning
confidence: 99%
“…It has been shown that objective functional tests are more robust against the influence of mental health status than a PROM. 1,25 Moreover, patients prefer performing an objective functional test over completing a battery of PROMs, perhaps because it provides direct and tangible feedback and is less time-consuming. 15 Considering these factors, the 5R-STS may constitute an excellent follow-up tool that could even be performed by patients themselves at home, either unsupervised or with televised supervision.…”
Section: Fig 4 Scatterplots With Marginal Histograms Showing Logarimentioning
confidence: 99%
“…Patient-oriented questionnaire scores, including the visual analog scale (VAS) for neck and arm pain and arm numbness, and the 36-item Short-Form Health Survey (SF-36), were performed preoperatively and at 6 months, 1 year, and 2 years postoperatively, and at 5 years if possible. The SF-36 is a 36-item scale measuring 8 domains of health-related quality of life: physical functioning (PF), physical role limitations (RP), bodily pain (BP), general health perceptions (GH), energy/vitality (VT), social functioning (SF), emotional role limitations (RE), and mental health (MH) 17 . The domain scores were then summarized as the physical component summary (PCS) and mental Mental well-being after laminoplasty 9 component summary (MCS) scores, according to an algorithm proposed by a previous report 18 .…”
Section: Clinical Evaluationmentioning
confidence: 99%
“…Lebow et al 28 argued that pain from disc herniation might contribute to preoperative depression and anxiety and that discectomy improves mental health and well-being during the postoperative period over months with improvement in anxiety and depression. Three studies showed level of depression measured preoperatively did not predict the surgical outcome 15 , 28 , 29 and that depression improved postoperatively in patients with a favorable outcome and did not improve in patients with a poor treatment outcome, suggesting that psychological disorders may be the result of DLSS related complaints 29 , 30 . However, other studies found preoperative depression to be associated with poorer life satisfaction after surgery 31 and poorer treatment outcome (symptom severity, disability and walking capacity) after surgery 31 , 32 .…”
Section: Discussionmentioning
confidence: 99%
“…Depression has been shown to negatively influence treatment efficacy in patients with DLSS 13 . The evidence on anxiety and the interaction between anxiety and depression is less well studied and conflicting 14 , 15 .…”
Section: Introductionmentioning
confidence: 99%